Badung’s Environment and Cleanliness Agency Law Enforcement Competency Certification Procedure: A Comparative Study with The Department of Environment in Australia - Kadek Indira Lokahita; I Gusti Ngurah Parikesit Widiatedja; Ni Gusti Ayu Dyah Satyawati (Pandecta Research Law Journal, 2023)
This research aims to develop quality human resources in the Environment and Cleanliness Agency of Badung Regency. The research also compares the Badung Environment and Cleanliness Agency workforce with the Environment Agency officers in Australia. As a law country, Indonesia requires support from various stakeholders, especially law enforcement officials. The definition of law enforcement officers in a narrow sense is the police, prosecutors, and judges, while in a broad sense it is defined by all officers in law enforcement institutions who have the authority to inspect, supervise or enforce laws. The holistic quality of law enforcement officers will build an ideal work ecosystem. In the current condition, many of them are involved in criminal actions such as corruption thus, they do not receive trust from the public. In addition, they are also considered less swift in supervising the community’s actions. That is because of the economic welfare, lack of education, and lack of workers at work. The legal research method used is normative, using a comparative approach and a statutory approach. Nowadays, Badung Regency conditions currently have many lodgings in Bali, Hence the challenge for the Badung Regency Environment and Cleanliness Agency to supervise the construction of the lodging place. The research findings show a challenge in the unequal quantity between officers in the field of supervision who have obtained certificates of competence at the Badung Regency Environment and Cleanliness Agency and the construction of thousands of hotels there. The total shortage of workers at the Badung Regency Environment and Cleanliness Agency is 12 (twelve) workers. While In Australia has sufficient labor and equal pay, especially in the environment department.